Zeolite growth over fiberglass for biogas enrichment - Medrado, Lucas; Rodrigues Loiola, Adonay (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Biogas, produced during anaerobic digestion processes of organic substrates from industrial, agricultural and sewage waste, is considered a promising alternative source of renewable energy [1]. It is mainly composed of CH₄ (50–70%), CO₂ (30–50%) and other gases in smaller quantities. The removal of CO₂ is a key stage for biogas to be commercially used. In this context, the adsorption of molecules on solid surfaces combined with the PSA method has been efficient in applications with several selective grade materials, such as membranes, titanosilicates, carbon molecular sieves, and silica gels. Zeolites, which are part of the tectosilicate subgroup, are well-known as efficient CO₂ adsorbents. This work aims to promote the growth of zeolite A on fiberglass by using nanozeolite A as seed to induce the controlled growth of zeolite crystals over the fiber surface giving rise to materials suitable to form cartridges to be used as columns for biogas enrichment. The fiberglass underwent an activation process that consisted of contact with NaOH solution for 72 h, under orbital stirring. Next, the fibers were impregnated were molded as cylinders and impregnated with nanozeolite which were dispersed in water. The seeded fiber was then submitted to zeolite growth by a hydrothermal treatment for 4h in. The gel composition used in the synthesis was 3.165 Na₂O: Al₂O₃ : 1.926 SiO₂ : 128 H₂O.The activation of the fiberglass by alkaline treatment was efficient in favoring the growth of zeolite type A crystals due to the increase of the roughness on the fiber surface, combined with the increase of silanol groups present in its filamentous structure, therefore compatible with the species present in the synthesis gel that give rise to the grown zeolite A. The X-ray diffractogram shows peaks consistent with zeolite A as well as the baseline distortion related to the amorphous nature of the fiberglass [2]. The scanning electron microcopy images allow the visualization of cubic crystals of zeolite A grown on the glass fiber, indicating the effectiveness of the experimental approach and shedding light to a possibly potential material to be applied in the removal of CO₂ in the enrichment process of biogas.